Peningkatan Kemampuan Berpikir Kritis Siswa Melalui Penerapan Model Pembelajaran Kooperatif Tipe Group Investigation Berbantuan Digital Mind Map: Improving Students' Critical Thinking Ability Through the Application of Group Investigation Type Cooperative Learning Model Assisted by Digital Mind Map - Deviani, Imas; Gumilar, Gugum; Sadiah, Ati (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
This research is motivated by the problems that occur at SMAN 5 Tasikmalaya, namely the low critical thinking ability of students. The method used is an experimental method with a type of pseudo-experiment, with a research design using a non-equivalent control group design, and data collection techniques through a description test. The population in this study was all class X SMAN 5 Tasikmalaya in the 2024/2025 school year which amounted to 470 students. The sample used was class X-9 which amounted to 34 people as an experimental class and class X-6 which amounted to 35 people as a control class with sampling using nonprobability sampling technique. The purpose of this study was to determine the effect of applying the cooperative learning model of Group Investigation type assisted by Digital Mind Map in improving students' critical thinking skills in economic subjects. Based on the results of the study, it is explained that there is an effect of the application of the cooperative learning model of Group Investigation type assisted by Digital Mind Map on students' critical thinking skills on the material of Financial Institutions in Indonesia, where Ha is accepted if the sig. (2-tailed) value ≤ 0.05 and based on research obtained a sig. (2 tailed) value of 0.000 <0.05. The average score of the experimental class is higher than the control class, thus it can be concluded in this study that the cooperative learning model of Group Investigation type assisted by Digital Mind Map can improve students' critical thinking skills.